Genome-Wide Characterization of PEBP Gene Family and Functional Analysis of TERMINAL FLOWER 1 Homologs in Macadamia integrifolia - Jing Yang; Conghui Ning; Ziyan Liu; Cheng Zheng; Yawen Mao; Qing Wu; Dongfa Wang; Mingli Liu; Shaoli Zhou; Liling Yang; Liangliang He; Yu Liu; et al. (Plants, 2023)
Edible Macadamia is one of the most important commercial nut trees cultivated in many countries, but its large tree size and long juvenile period pose barriers to commercial cultivation. The short domestication period and well-annotated genome of Macadamia integrifolia create great opportunities to breed commercial varieties with superior traits. Recent studies have shown that members of the phosphatidylethanolamine binding protein (PEBP) family play pivotal roles in regulating plant architecture and flowering time in various plants. In this study, thirteen members of MiPEBP were identified in the genome of M. integrifolia, and they are highly similarity in both motif and gene structure. A phylogenetic analysis divided the MiPEBP genes into three subfamilies: MFT-like, FT-like and TFL1-like. We subsequently identified two TERMINAL FLOWER 1 homologues from the TFL1-like subfamily, MiTFL1 and MiTFL1-like, both of which were highly expressed in stems and vegetative shoots, while MiTFL1-like was highly expressed in young leaves and early flowers. A subcellular location analysis revealed that both MiTFL1 and MiTFL1-like are localized in the cytoplasm and nucleus. The ectopic expression of MiTFL1 can rescue the early-flowering and terminal-flower phenotypes in the tfl1–14 mutant of Arabidopsis thaliana, and it indicates the conserved functions in controlling the inflorescence architecture and flowering time. This study will provide insight into the isolation of PEBP family members and the key targets for breeding M. integrifolia with improved traits in plant architecture and flowering time.